2017
DOI: 10.1136/bmjopen-2016-013053
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lapatinib and trastuzumab for HER2-positive breast cancer: a systematic review and meta-analysis of randomised controlled trials

Abstract: ObjectivesThe anti-HER2 monoclonal antibody trastuzumab and the tyrosine kinase inhibitor lapatinib have complementary mechanisms of action and synergistic antitumour actively in models of HER2-positive breast cancer. However, the efficacy of trastuzumab in combination with lapatinib remains controversial. Therefore, we conducted this meta-analysis to compare combination treatment with lapatinib and trastuzumab to trastuzumab or lapatinib alone in the treatment of HER2-positive breast cancer.MethodsRandomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Given this background, the activity of small molecules tyrosine kinase inhibitor, lapatinib, could be also studied in this molecularly selected group of diseases. 26 Targeted next-generation sequencing confirmed mutations in TP53, PIK3CA, CDKN2A, RB, ATM, HRAS and HER2 genes, previously described in two smaller series of SAC. 25,27,28 In addition, the use of a more extensive NGS panel, targeting 50 cancer-related genes, allowed us to reveal mutations in further genes such as NRAS, KRAS, MET, FBXW7 and FGFR3 in porocarcinoma, AKT1 in hidradenocarcinoma and APC or FLT3 in PDSAC.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Given this background, the activity of small molecules tyrosine kinase inhibitor, lapatinib, could be also studied in this molecularly selected group of diseases. 26 Targeted next-generation sequencing confirmed mutations in TP53, PIK3CA, CDKN2A, RB, ATM, HRAS and HER2 genes, previously described in two smaller series of SAC. 25,27,28 In addition, the use of a more extensive NGS panel, targeting 50 cancer-related genes, allowed us to reveal mutations in further genes such as NRAS, KRAS, MET, FBXW7 and FGFR3 in porocarcinoma, AKT1 in hidradenocarcinoma and APC or FLT3 in PDSAC.…”
Section: Discussionmentioning
confidence: 54%
“…Unfortunately, in our series we could not verify if in the HER2‐positive cases the score 2+ was sustained by gene amplification, which is mandatory for eligibility to anti‐HER2 monoclonal antibody. Given this background, the activity of small molecules tyrosine kinase inhibitor, lapatinib, could be also studied in this molecularly selected group of diseases …”
Section: Discussionmentioning
confidence: 99%
“…The increased activity of dual targeting of HER2, either through combinations of two different HER2-targeted antibodies or by use of a HER2-targeted antibody and TKI, has been shown to improve outcomes in preclinical studies and in patients with HER2 þ cancers (10,38). In this study, the combinatorial activity of tucatinib þ trastuzumab also produced improved antitumor activity in vivo in HER2 þ CDX and PDX xenograft models of breast, gastric, colorectal, and esophageal cancers.…”
Section: Mct First Disclosuresmentioning
confidence: 69%
“…A recent meta-analysis which included seven clinical trials concluded that the combination of trastuzumab and lapatinib can improve pCR, PFS and OS without added toxicity in patients with HER2-positive BC. This might indicate that large-scale trials and statistical power are needed to fully evaluate the efficacy of dual blockade regimens [24].…”
Section: Combination Regimensmentioning
confidence: 99%